2012
DOI: 10.1371/journal.pone.0034822
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Etiology of Atherogenesis – In Vitro Induction of Lipidosis in Macrophages with a New LDL Model

Abstract: BackgroundAtherosclerosis starts by lipid accumulation in the arterial intima and progresses into a chronic vascular inflammatory disease. A major atherogenic process is the formation of lipid-loaded macrophages in which a breakdown of the endolysomal pathway results in irreversible accumulation of cargo in the late endocytic compartments with a phenotype similar to several forms of lipidosis. Macrophages exposed to oxidized LDL exihibit this phenomenon in vitro and manifest an impaired degradation of internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(66 citation statements)
references
References 51 publications
2
61
0
3
Order By: Relevance
“…33 Moreover, macrophages play a crucial role in the progression and instability of atherosclerotic plaques. [34][35][36] Thus, promoting the clearance of macrophages from plaques is an alternative strategy for treating AS. SDT, which combines low-intensity ultrasound with different sonosensitizers, has been demonstrated to induce apoptosis in a variety of cell types relevant to different diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Moreover, macrophages play a crucial role in the progression and instability of atherosclerotic plaques. [34][35][36] Thus, promoting the clearance of macrophages from plaques is an alternative strategy for treating AS. SDT, which combines low-intensity ultrasound with different sonosensitizers, has been demonstrated to induce apoptosis in a variety of cell types relevant to different diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the release of metalloproteinase from macrophages could weaken the fibrous cap of the plaque and promote rupture. 35 Therefore, the antiapoptosis effects of macrophages in early-stage atherosclerotic lesions increase the likelihood of plaque development. 34 Our group previously confirmed that PpIX could enter athermanous plaques in the rabbit carotid artery.…”
mentioning
confidence: 99%
“…Macrophages, which accumulate in atherosclerotic plaques, play a crucial role in the occurrence of atherosclerosis [2,3]. Therefore, therapies targeting macrophages have been recognized as beneficial for plaque stability [4].…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, окЛНП оказывают влияние на развитие атеросклероза и при участии других меха-низмов. Модифицированные ЛНП ингибируют обра-зование эндотелиальными клетками фактора роста, стимулируют проникновение моноцитов в интиму, задерживают миграцию макрофагов из интимы [1,4,5]. Также окислительная модификация ЛНП зависит от их антиоксидантного потенциала.…”
Section: результаты и обсуждениеunclassified
“…Окислительная модификация циркулирующих в крови ЛНП менее выражена, чем в субэндотелии сосудистой стенки, где активны процессы клеточного окисления ЛНП моноцит/макрофагами, Т-лимфоци-тами и пенистыми клетками, секретирующими актив-ные кислородные метаболиты (АКМ) [4,5]. В сосудис-той стенке (интиме) часть ЛНП подвергается окисле-нию и преобразованию в модифицированные частицы.…”
unclassified